If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying B + 3 = b + 2 Reorder the terms: 3 + B = b + 2 Reorder the terms: 3 + B = 2 + b Solving 3 + B = 2 + b Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + B = 2 + -3 + b Combine like terms: 3 + -3 = 0 0 + B = 2 + -3 + b B = 2 + -3 + b Combine like terms: 2 + -3 = -1 B = -1 + b Simplifying B = -1 + b
| -6b-6b=-24 | | 1x+5y=20 | | 2b+10=b+2 | | 2b+10=b+3 | | C-5d=2 | | 4b-2=18 | | 5,300f-3,200=f | | x^3-x^4-2x^2=0 | | 4x-8x=4 | | 5x+10=9x+2 | | x+10=5(x-10) | | 6x-8-8x=8 | | 9=-v+2+8v | | x+5+1=-2 | | -(8x+4)=6(2x+1) | | -12=4-7p-p | | 7(s-4)=42 | | -3x+1=-2x-9 | | 0=15+2m | | 10u-21=-8u+18 | | 3b-4=2b+10 | | 2(4-1,9z)=0,8-0,2z | | 2(4x+10)=2x+-4 | | .26=ln(x) | | 6(x+4)=3(4x+2) | | 28y+3=47 | | 11y+6x=17 | | 40x+16(1.5x)=630.00 | | 6-(2w+1)=5w-2(5+w) | | -15X+5=-9x-21 | | 6(2m-5)-2(5-2m)=15+6(m+1) | | log(4x+5)=2 |